Penerapan Lean Manufacturing dan Analisis 5W+1H Dalam Upaya Mengurangi Waste Proses Produksi Frame Chassis di PT. OC - Husein, Doni All Sadam; Wahyudin (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
OC is one of the manufacturing industries engaged in automotive, one of its products is Frame Chassis. In the Frame Chassis production process there is a problem that often occurs a production line stop which eventually causes the daily production target not to be reached. This research aims to reduce waste that occurs in PT. OC, especially in the line that produces Frame Chassis by using the Lean Manufacturing concept, namely the VSM (Value Stream Mapping) method and OEE (Overall Equipment Effectiveness) calculation. The results obtained based on the calculation and analysis results were 10 total delay type activities with a total time of 1457 seconds or equivalent to 24 minutes 28 seconds obtained 16% and obtained 5 Non Value Added activities, with a total time of 1175 seconds or equivalent to 19 minutes 58 seconds obtained a percentage of 13%. In addition, from the identification of waste carried out there are 3 types of waste  that. From the data processing results above researchers gave proposed improvements with 5W + 1H analysis. Keywords : 5W + 1H Analysis, Lean Manufactuing, Process Activity Mapping (PAM), Seven Waste, Value Stream Mapping (VSM).